Sequence stratigraphy and paleogeographic setting of the Antimonio Formation (Late Permian-Early Jurassic), Sonora, Mexico - Carlos M. González-León (Revista Mexicana de Ciencias Geológicas)
The Antimonio Formation is a Late Permian, Triassic and Early Jurassic sedimentary succession composed of 14 fining-upwards unconformity-bounded sequences. It contains the Permian-Triassic and Triassic-Jurassic systemic boundaries, which are represented as well-marked disconformities… in order to continue, download the full paper in PDF.